(3JUqhQGJ GdeYqde Mhd OhQ GdeQTO GdJQHhqj aj GdeQMdI GdEHJOGFjI aj HYV eOGQS LfhH dHfGfs - (3Hh MjOQ, cGQhdjfs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2008)
(3gOaJ gPg GdOQGSI Edi JSdjW GdVhA Ydi NOeI GdEQTGO GdJQHhj hGdJj JJeKd HYdGbI GdeYde HGdeQTO aj MGd hLhOg hHeeGQSI hXjaI GdEQTGO aj MGd ZjGH ecJH GdEQTGO hGdJhLjg aj GdeOGQS, hPdc YHQ OQGSI ejOGfjI EMUGFjI bOeJ ajgG GSJeGQGJ Edi eYdej GdeQMdI GdGHJOGFjI aj CQHY eOGQS aj eMGaXI GdLfhH(B. (3HjfJ fJGFL GdOQGSI Cf eYdej GdYjfI jedchf eYdheGJ cGajI Mhd eaGgje GdEQTGO GdJQHhj hjDefhf HVQhQI hLhOg aj GdeOQSI deG dg ef OhQ aYGd aj YedjI GdJhLjg(B. (3hCLeY GdeYdehf aj eNJda GdeOGQS GdCQHY Zdi GdJGKjQ GdSdHj dZjGH GdJhLjg hGdEQTGO Ydi GdJMUjd GdOQGSj ddJdejP(B. (3hNdUJ GdOQGSI Edi eOi CgejI hMGLI GdeOQSI dhLhO GdeQTO GdJQHhj Ydi UYjO GdeQGMd GdJYdjejI cGaI hEfTGA GdCLgRI GdJj JNJU HGdJNWjW dg hGdETQGa Ydi JfajPg aj LejY GdeOGQS GddHfGfjI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Cycle primaire; Elementary Education; Orientation et Conseil; School guidance and counseling; South; Sud; (3GdJhLjg hGdEQTGO GdeOQSjs; (3GdLfhHs; (3GdeQMdI GdGHJOGFjIs